Subtype diagnosis, treatment, complications and outcomes of primary aldosteronism and future direction of research: a position statement and consensus of the Working Group on Endocrine Hypertension of the European Society of Hypertension - Mulatero, Paolo; Sechi, Leonardo A; Williams, Tracy Ann; Lenders, Jacques W M; Reincke, Martin; Satoh, Fumitoshi; Januszewicz, Andrzej; Naruse, Mitsuhide; Doumas, Michael; Veglio, Franco; Wu, Vin Cent; Widimsky, Jiri (Journal of hypertension, 2020)
: Primary aldosteronism is a frequent cause of secondary hypertension requiring a specific pharmacological treatment with mineralocorticoid receptor antagonist or with unilateral adrenalectomy. These treatments have shown to reduce the excess of cardiovascular risk characteristically associated with this disease. In part I of this consensus, we discussed the procedures for the diagnosis of primary aldosteronism. In the present part II, we address the strategies for the differential diagnosis of primary aldosteronism subtypes and therapy. We also discuss the evaluation of outcomes and provide suggestions for follow-up as well as cardiovascular and metabolic complications specifically associated with primary aldosteronism. Finally, we analyse the principal gaps of knowledge and future challenges for research in this field.
Keywords: adrenalektomie; Adrenalectomy; Consensus; Mineralocorticoid Receptor Antagonists; hypertenze; lidé; Hyperaldosteronism; Hypertension; hyperaldosteronismus; konsensus; antagonisté mineralokortikoidních receptorů; Humans